EFFECT OF GA3 AND PROPAGATION MEDIA ON GERMINATION, GROWTH AND VIGOUR OF PAPAYA CV. COORG HONEY DEW - VIKAS RAMTEKE; D. H. PAITHANKAR; EKTA P. NINGOT; VIVEK KUMAR KURREY (The Bioscan, 2015)
An experiment was conducted during 2013-14 to study the influence of GA3 and growing media on seed germination and seedling growth of papaya. The treatments comprised combinations of soil, sand, FYM, cocopeat and vermicompost with varing levels of GA3. Altogether, 21 treatments were applied in a Factorial completely randomized block design with three replications. The result indicated that GA3 200 ppm is found to be the most effective for better germination of papaya seeds as well as growth of papaya seedlings (height of the seedling, average leaf area, stem diamter, length of tap root, fresh and dry weight of seedlings as well as survival per cent of seedlings). Among different growing media soil + FYM (1:1) recorded higher values for germination percentage, seed vigour index, height of the seedling, number of leaves, average leaf area, stem girth and length of tap root, whereas maximum shoot and root weight and survival percentage was noticed in soil: sand : cocopeat: vermicompost (1:1:1:1) media. The treatment combination of GA3 200 ppm and growing media soil: sand: cocopeat: vermicompost (1:1:1:1) showed higher germination per cent, seed vigour index, average leaf area, length of tap root and survival percentage. Therefore, the combination of GA3 200 ppm and growing media soil + sand + cocopeat + vermicompost (1:1:1:1) was found most suitable for growing of papaya nursery.